Enrichment of NaCl-reduced burger with long-chain polyunsaturated fatty acids: Effects on physicochemical, technological, nutritional, and sensory characteristics - Rios-Mera, Juan D. (2021)
This study aimed to determine the effect of NaCl reduction and addition of long-chain polyunsaturated fatty acids (PUFA) on the quality traits of burgers. Fish oil was either directly incorporated or added as encapsulated by freeze-dried microparticles (complex coacervates) composed of soy protein isolate and inulin. Despite the differences in some parameters associated with NaCl reduction (e.g., instrumental hardness), the quality of the burgers was mainly affected by the microparticles. Thus, a decrease in pH and increase in hardness and chewiness were observed, and a higher exposure of fish oil to oxidation was observed thus increasing volatile oxidation compounds and negatively impacting on the sensory profile and overall liking of the burgers. However, the encapsulation of the fish oil helped to retain EPA and DHA after cooking. The results of the NaCl-reduced burger with unencapsulated fish oil suggest the possibility of incorporating PUFAs, but only containing EPA after cooking. © 2021 Elsevier Ltd